2019
DOI: 10.3390/molecules24162887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Portulaca Oleracea Extract on Acute Alcoholic Liver Injury of Rats

Abstract: The present study was envisaged to investigate the chemical constituents and the intervention effects of Portulaca oleracea extract (POE) on acute alcoholic liver injury of rats. The chemical composition of POE was detected by high performance liquid chromatography (HPLC). Sixty male Wistar rats were divided into 6 groups: Normal control (NC) group, acute alcoholic liver injury model group (ALI), low, medium and high dose of POE (25, 50, 100 mg/kg) groups and bifendate (BF, 3.75 mg/kg) group. Each group was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…IFN-γ is a pro-inflammatory cytokine that enhances the sensitivity of liver cells to TNF-α, making liver cells more easily damaged [44]. The oxidative stress state after liver injury causes an imbalance in inflammatory factors, including TNF-α and IL-6 in the body, leading to an increase in TNF-α and IL-6 in the liver [45]. LP-HFY05 reduced liver injury by regulating the levels of IL-6, IL-12, TNF-α, and IFN-γ in the serum of liver-injured mice, which was a similar effect as silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is a pro-inflammatory cytokine that enhances the sensitivity of liver cells to TNF-α, making liver cells more easily damaged [44]. The oxidative stress state after liver injury causes an imbalance in inflammatory factors, including TNF-α and IL-6 in the body, leading to an increase in TNF-α and IL-6 in the liver [45]. LP-HFY05 reduced liver injury by regulating the levels of IL-6, IL-12, TNF-α, and IFN-γ in the serum of liver-injured mice, which was a similar effect as silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that P. oleracea enhanced the antioxidant potential and relieved the liver cells from inflammatory injury which was induced by ethanol. P. oleracea extract treatment also decreased the expression of miR-122 47 . MiR-122 is micro RNA.…”
Section: Pharmacological Activitiesmentioning
confidence: 90%
“…It is the second-largest liver disorder after viral hepatitis. Work was done to know the effectiveness of P. oleracea in treating the acute alcoholic liver injury in rats 47 . Flavonoids like hesperidin, myricetin, rutin and quercetin were detected in P. oleracea extract with the help of high performance liquid chromatography.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-γ is a proinflammatory cytokine and can enhance the sensitivity of liver cells to TNF-α, rendering liver cells susceptible to damage [34]. Oxidative stress appearing after liver tissue injury can cause an imbalance in inflammatory factors, including IL-6, IL-12, TNF-α, and IFN-γ, in the body, thus increasing their contents in the liver [35]. WPPs can alleviate liver injury by regulating the serum levels of IL-6, IL-12, TNF-α, and IFN-γ in mice with liver injury, and the effect is similar to that of silymarin.…”
Section: Discussionmentioning
confidence: 99%